Internet Literature: Increasing Information Competence in the Learning Process of Students of Class 7 Middle School - Putri Fadillah; Asep Bayu Dani Nandiyanto; Tedi Kurniawan; Muhammad Roil Bilad (Universitas Pendidikan Indonesia (UPI), 2022)
Internet literacy is very influential in today's social life. Even with students who carry out the learning process at home. This research was conducted to understand the extent to which students can formulate the information needs they get from the internet, as well as knowing the improvement of student competence based on information obtained from the internet for the learning process. The research method carried out by us is qualitative descriptive using a questionnaire and a post-questionnaire as the research medium. The results obtained from this study are students experience an increase in information competence that can help during the learning process.